THE EFFECT OF CIPLUKAN EXTRACT (Physalis angulata L.) AS ANTIPSORIATIC AND TO LYMPHOCYTES COUNT OF SKIN TISSUE IN PSORIASIS MICE MODEL - Putri Nur'afni Sa'adah; Thianti Sylviningrum; Dody Novrial; Fajar Wahyu Pribadi; Wahyu Dwi Kusdaryanto; Muhamad Salman Fareza (Mandala Of Health, 2021)
ABSTRACT Psoriasis is a chronic skin disease in form of papule-shaped lesion and erythematous plaques with thick white scales. The pathogenesis of psoriasis involves IL-23/Th-17 cytokine pathway that contributes the activation of T-lymphocytes and proinflammatory cytokines. Treatment of psoriasis using methotrexate has inhibitory effect of the synthesis of nucleic acid towards T-lymphocytes and keratinocytes. Ciplukan (Physalis angulata L.) has anti-inflammatory potential effect which contains steroid, flavonoid, alkaloid, and physalin that may inhibit lymphocyte activation and proinflammatory cytokine production. The study is used the method of experimental study with post test only with control group design. Thirty five female mices were divided into 7 groups. The parameters of this study is anti-psoriatic (PASI and Baker’s score) and lymphocytes count in psoriasis mice model. The results of Kruskal-Wallis, PASI and Baker’s score showed that p=0,001 (p<0,05) and the result of lymphocytes count using One Way ANOVA showed that p=0,001 (p<0,05). The 800 mg/kgBW dose of ciplukan extract showed the largest decrease on PASI score and lymphocytes count, and the 1200 mg/kgBW dose one showed the largest decrease on the Baker’s score. The present of the 800 mg/kgBW dose of ciplukan extract gives the most optimal effect in reducing PASI score and skin tissue lymphocytes count in psoriasis mice model that were not significantly different with the treatment control group, while 1200 mg/kgBW dose one gives the most optimal effect in reducing Baker’s score that were significantly different with the treatment control group. Keywords: Ciplukan extract, lymphocytes, methotrexate, Physalis angulata L